Reported Barriers to Hepatitis C Treatment among Pregnant and Early-Parenting Mothers Undergoing Substance Use Disorder Treatment in One U.S. State - Ayooluwatomiwa Deborah Adekunle; Kathi L. Harp; Zaynab G. Al-Abdali; Agatha S. Critchfield; Sheila Barnhart; Kathleen T. Winter (Infectious Disease Reports, 2021)
Nationwide, the prevalence of the hepatitis C virus (HCV) has risen in recent years. At least 90% of infected persons must be treated to achieve global elimination targets. The current study aimed to explore barriers to, and facilitators of, direct-acting antiviral (DAA) HCV treatment uptake amongst pregnant and early-parenting women undergoing comprehensive substance use treatment. Twenty participants with documented HCV antibody positivity were recruited from two substance use treatment centers in central Kentucky. Semi-structured interviews were conducted to explore knowledge about HCV, previous experiences, and intentions to seek care. Themes were extracted using an inductive analytical approach. Most participants were aware of the dangers posed by HCV infection. However, there was a high degree of misinformation about transmission mechanisms and treatment eligibility requirements. Low priority for HCV treatment also surfaced as a barrier to treatment uptake. Participants reported being unable to seek care due to time and resource limitations in the presence of a highly demanding treatment process. Findings from the current study suggest that more work is needed to eliminate residual barriers that limit access to HCV treatment among pregnant and early-parenting women in treatment for substance use disorder.